2004
DOI: 10.1158/0008-5472.can-03-1672
|View full text |Cite
|
Sign up to set email alerts
|

α7-Nicotinic Acetylcholine Receptors Affect Growth Regulation of Human Mesothelioma Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 33 publications
3
82
0
3
Order By: Relevance
“…TNF administered simultaneously, as reported by different authors 33 and in our previous articles, 25,32 increased the level of DNA-SSB (under-deproiteinizing condition) induced by CPT. In MSTO-211H cells, SN38 (1-hour treatment at the IC 50 ) induced DNA breaks, as shown in Figure 2.…”
Section: Determination Of Dna Single Strand Breakssupporting
confidence: 78%
See 1 more Smart Citation
“…TNF administered simultaneously, as reported by different authors 33 and in our previous articles, 25,32 increased the level of DNA-SSB (under-deproiteinizing condition) induced by CPT. In MSTO-211H cells, SN38 (1-hour treatment at the IC 50 ) induced DNA breaks, as shown in Figure 2.…”
Section: Determination Of Dna Single Strand Breakssupporting
confidence: 78%
“…33 Briefly, adherent cells and detached cells were harvested separately, washed, and lysed with 50 mmol/L Tris, pH 7.5; 10 mmol/L EDTA; 0.5% Triton-X-100; and 0.5 mg/mL proteinase K for 2 hours at 50°C. Samples were then extracted twice with phenol/chloroform/ isoamyl alcohol and precipitated with ethanol.…”
Section: Internucleosomal Dna Fragmentationmentioning
confidence: 99%
“…This contention is supported by the findings that nicotine can prevent apoptosis induced by various agents, thus conferring a survival advantage as well (10,(50)(51)(52). Elucidation of the signaling events mediated by nAChRs present on nonneuronal cells may open new avenues for targeting cancer therapy, focusing on agents that inhibit the β-arrestin-Src signaling axis or Rb-Raf-1 interaction.…”
Section: Discussionmentioning
confidence: 92%
“…El-Sokkary et al [2] reported that the lung is the chief organ which is highly liable to free radical generation after cigarette smoke. Also, Trombino et al [47] and Luqman and Rizvi [48] observed interstitial infiltration of inflammatory cells, degenerative changes of both and alveolar epithelium and interstitial cells in addition to interstitial infiltration of inflammatory. These changes could be explained by chronic inflammation caused by NIC administration [49].…”
Section: Discussionmentioning
confidence: 95%